“Madanadha” The Dramatic Tone Poem for Chamber Orchestra - Okkitchawat, Woracha; Premananda, Weerachat (Rangsit Music Journal, 2022)
“Madanabadha” the dramatic tone poem for chamber orchestra is the Master Degree’s composition inspired by the Royal Literature “Madanabadha” of the late King Vajiravudh, Rama VI. The music composition is intended to portray the story and express the feeling by adopting theoretical and technical approaches into dramatic and harmonic music in a format contemporary musical style which harmoniously blends Western and Eastern music. In addition, a traditional Thai musical form was further developed to create imaginative love story in different emotional angles. A duration of this chamber music composition is approximately 20 minutes which is divided into 4 movements. The composition was composed using Tonality together with Pentatonic Scale and Mode, reflecting uniqueness of Thai musical style. Harmonic progressions were meticulously arranged to show essential dimension of tone center